Prevalence of suicidal ideation and attempted suicide amongst women and girls in South Asia: A systematic review and meta-analysis - Hoimonty Mazumder; Tony Lugemwa; Md Monir Hossain Shimul; Easter Protiva Gain; M. Mahbub Hossain; Kenneth D. Ward (Psychiatry Research Communications, 2022)
A growing body of literature suggests an increased risk of suicidal ideation and attempted suicide among women and girls in South Asia. This systematic review and meta-analysis aimed to appraise the current evidence and estimate the prevalence of suicidal ideation and attempted suicide in this population. We systematically searched nine (9) bibliographic databases (PubMed, ASU, Embase, WoS, CINAHL, PsycInfo, PsycArticles, HSNE, and NAHC) and additional sources through December 17, 2021, for studies that reported the prevalence of suicidal ideation or attempted suicide. Random-effect models were used to estimate pooled prevalence.Of 30 eligible studies, 27 reported suicidal ideation and 12 reported attempted suicide. The pooled prevalence of overall suicidal ideation and attempted suicide were 17% (95% CI:14.00–20.00, n ​= ​39674) and 5% (95% CI: 4.00–7.00, n ​= ​20791), respectively. Thirteen studies enrolled adult women from the general population, nine recruited adolescent girls, and eight recruited female medical/university students. The pooled estimate of suicidal ideation was higher among adults, whereas attempted suicide was found to be higher among adolescents. These findings on suicidal ideation and attempted suicide suggest a heavy epidemiological and psychosocial burden among South Asian women and girls that necessitates a gender-sensitive integrated multi-sectoral approach.